7th International Electronic Conference on Sensors and Applications 2020
DOI: 10.3390/ecsa-7-08245
|View full text |Cite
|
Sign up to set email alerts
|

A Data Cleaning Approach for a Structural Health Monitoring System in a 75 MW Electric Arc Ferronickel Furnace

Abstract: Within a model of scientific and technical cooperation between the smelting company Cerro Matoso S.A. (CMSA) and the Universidad Nacional de Colombia (UNAL), a project was developed in order to take advantage of the data that were obtained from a sensor network in a ferronickel electric arc furnace at CMSA to improve the structural health monitoring process. Through this sensor network, online data are obtained on the temperature measurement along the refractory lining of the electric furnace, as well as heat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Several data preprocessing steps were performed to detect abnormal behavior in the used variables. These data preprocessing steps are listed below [32] After verifying the data preprocessing, it was concluded that the 49 variables used to train and test the models did not present abnormal behaviors.…”
Section: Dataset For Validationmentioning
confidence: 99%
“…Several data preprocessing steps were performed to detect abnormal behavior in the used variables. These data preprocessing steps are listed below [32] After verifying the data preprocessing, it was concluded that the 49 variables used to train and test the models did not present abnormal behaviors.…”
Section: Dataset For Validationmentioning
confidence: 99%
“…Recently, different studies related to signal processing and data acquisition systems to monitor the state of furnaces and their lining inside CMSA have been developed. A work related to data preprocessing to handle a large amount of operation data in the CMSA furnaces presents a set of rules and filters in order to detect variables with anomalies and outliers 26 . Another work related to the development of a predictive temperature model based on deep learning time series reached low mean square error errors, predicting accurately temperatures in different sectors of the furnace 27 .…”
Section: Introductionmentioning
confidence: 99%
“…A work related to data preprocessing to handle a large amount of operation data in the CMSA furnaces presents a set of rules and filters in order to detect variables with anomalies and outliers. 26 Another work related to the development of a predictive temperature model based on deep learning time series reached low mean square error errors, predicting accurately temperatures in different sectors of the furnace. 27 In the process of shut down and initialize again the furnace, a contraction and expansion process of the hearth lining occurs; to measure the possible gap formation, an ultrasound-based method was deploy in the work of Tibaduiza et al in 2020.…”
mentioning
confidence: 99%